The Future to Conservation of Ramsar Sites: Environmental Education And Awareness - Shah, Parita; Atisa, George (Academia Kenya, 2021)
Kenya signed the Ramsar Convention on October 5, 1990, and ratified it on June 5, 1991. Today, Kenya has six Ramsar sites, namely Lakes Nakuru, Naivasha, Baringo, Bogoria, Elementaita and River Tana. To successfully implement the RC goals, the country has developed several legal frameworks and policies that are designed to create awareness and educate communities on the value of protecting wetlands. These include the Wetlands Conservation and Management Policy (GoK, 2015), Wetlands Conservation and Management Act (GoK, 2013b), Environment Policy (GoK, 2013a), Sessional Paper No. 6 on Environment and Development (GoK, 1999), the National Constitution of Kenya (GoK, 2010) and the Environmental Management and Coordination (Conservation and Management of Wetlands) Amendment Regulations (GoK, 2017). By 2012, when CoP 12 was held in Romania, Kenya had developed a national plan, including sub-national plans, basin-level plans and site-related plans, in line with the CEPA programme.
Keywords: Kenya; Ramsar Sites